Polyol-mediated synthesis of Bi-deficient Mg2+-doped sodium bismuth titanate and study of oxide ion migration behavior with functional properties - Singh P.; Pandey R.; Singh P. (My University, 2025)
Sodium Bismuth Titanate, Na0.5Bi0.5TiO3 (NBT) is considered as a probable lead-free piezoelectric material. But its acceptor-doped perovskite turns out as an outstanding oxide-ion conducting system with possible utilization in intermediate-temperature solid oxide fuel cells (IT-SOFCs). Also, the Bi-deficit Sodium Bismuth Titanate (Na0.5Bi0.5−xTiO3-δ) exhibits a notable oxide-ion conductivity. In the present investigation, the Bi-deficient and Mg2+-doped Sodium Bismuth Titanate (Na0.5Bi0.49Ti1−xMgxO3-δ; x = 0.00, 0.01, 0.02, 0.03) were first time synthesized via polyol mediated synthesis route at lower temperature with better surface area and good conductivity. The Mg2+ doping at Ti4+ site improved the sinterability and augmented the grain size. The structural, microstructural, textural and most importantly electrical properties were analyzed using XRD, Raman, FTIR, SEM, BET, TGA, and EIS techniques to gain understanding about effects of substitution of Mg2+ on structural behavior and electrical conductivity. We also explored the influence of Bi-deficient Mg2+-substituted NBT compositions on the oxygen vacancies and ion migration behaviors. A correlation among the phase formation, conduction behavior and ion diffusion mechanism has been established for the Mg2+ substituted Bi-deficit NBT derived compositions. The conductivity was found to be maximum for NBT4902 composition over the entire temperature range. Though at the higher doping concentration of Mg2+ (x > 0.02), conductivity was found to slightly decrease. © 2020 Elsevier B.V.